AKTIVITAS EKSTRAK ETANOL DAUN SALAM [Syzygium polyanthum (Wight) Walp.] SEBAGAI PENGHAMBAT ENZIM α-GLUKOSIDASE DAN STUDI SECARA IN SILICO - Rakhmat Ramdhani Alwie; Esti Mumpuni; Lilik Sulastri; Partomuan Simanjuntak (Jurnal Fitofarmaka Indonesia, 2021)
Diabetes Mellitus (DM) is a degenerative disease that can cause various complications such as cardiovascular, stroke, and hypertension. Antidiabetic drugs that are commonly circulated in the market, have side effects that can harm other organs such as liver, kidneys and other organs. Bay leaves have properties as inhibitors of the α-glucosidase enzyme in vitro and in vivo. The aims of this study was determine the activity of ethanolic extract of bay leaves by ultrasonic extraction method in inhibiting the α-glucosidase enzyme in vitro and in silico. Bay leaves were extracted using 70% and 96% ethanol by ultrasonic method for 15 minutes, and filtered and concentrated using a rotary vacuum evaporator 4 times. The extract obtained was tested for phytochemical content and the activity of α-glucosidase inhibitory assay. The extract with the best IC50 value was then separated using column chromatography (SiO2, dichloromethane, methanol) and produced 7 fractions and tested for α-glucosidase enzyme inhibition. The best fraction (fraction 6) was analyzed by Liquid Chromatography Mas Spectra (LCMS-MS). The results showed that bay leaf extract containing alkaloids, flavonoids, tannins, steroids, phenols, and fraction-6 had the best IC50 of 30.82 ppm. The results of LCMS-MS analysis of chemical compounds as inhibitors of the α-glucosidase enzyme were delphinidin (m/z 303) and had a rerank score of -75.59. In the in silico test using PLANTS docking software.